THE OBJECTIVES OF MONETARY POLICY AND THE CENTRAL BANKS’ ACTIVITY (Journal of Economic Research & Business Administration, 2018)
This article deals with the revision of the main targets of monetary policy. Monetary instruments ofregulation become main factors that influence on the economic entities and ensure conditions for theirinvestment and economic activity. Central banks, being responsible for monetary policy, provide dailystruggle against inflation, market volatility and financial system’s instability. Central banks in their activitychoose main priorities of the monetary policy aiming to establish a price stability, an effective level ofmoney supply and circulation, payment system development etc.High level of inflation in Kazakhstan; weakness of tenge; exchange rates’ unpredictable behavior;price volatility of financial instruments on the internal market; instability of local banking system; as well asbusiness units and households suffering from “expensiveness” of money – evidence about deep problemsin financial system and on money market. Stated problems specify the relevance of the research and determinesscientific interest to monetary policy in Kazakhstan and in foreign countries. Main purpose of theresearch is to clarify core principles of monetary policy and adopt them to the needs of national economy.